TEKNOLOGI PROSES PELENGKUNGAN ROTAN SECARA KIMIA UNTUK BAHAN BAKU MEBEL - Arsad, Effendi (Kementerian Perindustrian, 2011)
ABSTRACTThe research was design to know the impact of chemical compound in deflexioning process of the rattan for furniture material. There are three kinds of rattan using for this research. They are manau ( Calamus manna Miq.), batang (Daemonorops robusta Warb.) and suti (Calamus ormatus BI). The chemical compounds that used in this research are Natrium Hidroksida ( NaOH) and Dimetylsulfoxside ( DMSO). The result of water content is 12,98%. and this fulfilled the requirement for the funiture material which is 14%. The higher of the NaOH and DMSO concentration used is causing the increasing of rattan density. The same effect is shown in the bending strength ( MOR) and elasticity strength ( MOE), the higher of the chemical compound concentration is cause the rattan more easy to deflex.Keywords: rattan, plastisation, deflexion NaOH, DMSO, funiture